STRATEGI GURU DALAM MENGEVALUASI PEMBELAJARAN DENGAN APLIKASI KAHOOT DI UPT SD NEGERI SINAR MULYO - Deki Saputra; Krisno Budi Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teacher strategies in evaluating learning using the Kahoot Application at UPT SD Negeri Sinar Mulyo, as well as to analyze the obstacles faced and the effectiveness of the strategies applied. The method used is descriptive qualitative research with the research subjects being grade IV teachers. Data collection techniques in this study were carried out through interviews, observations, and documentation, while data analysis techniques used data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that teachers have a good understanding of Kahoot and have integrated it into the learning process since 2021. Thorough preparation was carried out by compiling question grids and integrating Kahoot with Google Classroom. In its implementation, Kahoot was used as a formative evaluation and ice-breaking tool, which succeeded in creating an interactive classroom atmosphere. Although there were obstacles such as internet network problems, teachers were able to overcome them by changing service providers and taking technology training. The effectiveness of using Kahoot can be seen from the increase in student participation and motivation. This study concludes that Kahoot is an effective evaluation tool in increasing student engagement, and provides recommendations for ongoing training for teachers and improving technology infrastructure in schools.